A social and political pact for Education - Juan López Martínez (ADIDE Federación, 2010)
Different organizations with social concern as well as all the social segments involved in education have requested for over ten years through different documents and speeches a contract for education that avoids that a change in the political orientation of successive governments takes alongside a change in the educational regulations after a short time. Education must be tackled as a matter of state, with a compromise between the two main political parties, so that changes in the government do not prevent to maintain the basic strategies and the sustainable financing of education.